PENGARUH PROFITABILITAS TERHADAP HARGA SAHAM PADA PT METRODATA ELECTRONICS TBK PERIODE 2009-2023 - Inayah, Nurfatinah; Puji Muniarty (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of profitability on stock prices at PT Metrodata Electronics Tbk for the period 2009–2023. The data used in this study are secondary data obtained from the company's financial statements. The analytical methods used include descriptive statistics, normality test, coefficient of determination, and simple linear regression. The results show that descriptively, profitability and stock prices fluctuated during the observation period. The normality test results indicate that profitability data are normally distributed, while stock price data are not normally distributed. The coefficient of determination shows that profitability contributes 20.6% to stock prices, while the remaining 79.4% is influenced by other variables outside this study. The regression results indicate that profitability has a positive but not significant effect on stock prices. Based on these findings, it can be concluded that profitability does not have a significant effect on stock prices at PT Metrodata Electronics Tbk for the period 2009–2023.